Harmonic Analysis of Tides for 7 Days of Hourly Observations - Franco, A. Dos Santos (The International Hydrographic Review, 2015)
In 1961 the International Hydrographic Bureau distributed to States Members the pamphlet "Análise Harmónica da Maré — 7 dias" (Harmonic Analysis of Tides — 7 Days), published by the "Diretoria de Hidrografia e Navegação" (Brazilian Directorate of Hydrography and Navigation). The pamphlet was my work, and I believed I had produced something useful from the surveyor’s point of view. However the results obtained with this method were sometimes discouraging. In 1963 Captain Langeraar, Hydrographer of the Royal Netherlands Navy, wrote me that very poor results were obtained by using the abovementioned method, and requested my comments on the matter. I replied by stating that I was very pleased to learn that the Netherlands Hydrographic Department was interested in studying this short period method of analysis. I am now pleased because, due to the theoretical research done by the Netherlands tidal experts, the Senior Civil Hydrographic Officer W. C. Wernink and Engineer Lieutenant M. Hendrikse of the Royal Netherlands Navy, one can see that the fundamentals of the method hold good, and that the poor results obtained arose from some numerical errors in the distributed pamphlet. In fact the excellent work done by the Netherlands Hydrographic Office now allows rectification of these errors. A good agreement was then found between the real tidal curve and the predicted curve obtained by using the harmonic constants from the analysis. It would be very desirable to make corrections to this pamphlet, for without them the users will certainly run into the same difficulties. I thought, however, that it would be better to take this opportunity to present a new edition of this work, in which I can develop several more modern theoretical concepts.